1990
DOI: 10.1001/archderm.1990.01670350092016
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Occurrence of Bullous Mastocytosis (Diffuse Cutaneous Mastocytosis)

Abstract: We studied four patients (a mother, her two daughters, and her son) with bullous mastocytosis, or diffuse cutaneous mastocytosis, whose genetic inheritance suggested an autosomal dominant pattern. The clinical characteristics included extensive bullae, numerous urticaria, pruritus, flushing, and pseudolichenified skin over all body surfaces without systemic organ involvement. The histopathologic findings disclosed a pronounced accumulation of mast cells in the dermis. Electron microscopic studies of lesional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 18 publications
2
9
0
2
Order By: Relevance
“…Since it is often associated with systemic mastocytosis, multiple organs may be affected [1][2][3]. In our case, diffuse érythro dermie cutaneous mastocytosis was associated with bone marrow involvement.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Since it is often associated with systemic mastocytosis, multiple organs may be affected [1][2][3]. In our case, diffuse érythro dermie cutaneous mastocytosis was associated with bone marrow involvement.…”
Section: Discussionmentioning
confidence: 66%
“…It was found that histamine-1-or histamine-2-blocking agents [3,8], cro molyn sodium [9] and topical steroid ointments [ 10] can be effective in relieving the symptoms. Since antihistaminic treatment was not effective in our case, ketotifen was added to her treatment, because it has been found effective in some patients with mastocytosis [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentialdiagnostisch muß an Dermatitis herpetiformis, bullöse Impetigo, chronisch bullöse Erkrankung miliäres Vorkommen (autosomal-dominant) [14], solitär noduläre und multiple makulopapulöse sowie diffuse bullöse Formen wurden beobachtet [2,4,17]. Die Blasen entstehen offensichtlich durch Freisetzung biologisch aktiver Substanzen [1, 3] aus Granula der Mastzellen, die mittels Giemsa-und Toluidinblaufärbung histologisch nachgewiesen wurden.…”
Section: Introductionunclassified